1977
DOI: 10.3758/bf03198725
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of shock aversion thresholds during the menstrual cycle

Abstract: Aversion thresholds for electrical shock were obtained from 5 males, 6 females who were taking oral contraceptives, and 12 females who were not. All subjects were volunteers from introductorylevel psychology courses. Measures were repeated 3 times per week for 5 weeks. Males and females taking oral contraceptives showed no cyclic fluctuations in threshold. The other female group had significant (p < .025) fluctuations in threshold, from a maximum at ovulation to a minimum 1 week after the onset of the menses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
2

Year Published

1980
1980
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 10 publications
0
29
0
2
Order By: Relevance
“…In contrast, a higher threshold and tolerances in the premenstrual phase have been found by Aberger et al [1983] who used the muscle ischaemia task [84]. It is revealed that that the highest level of pain sensitivity was one week following menstruation (days 1-7), and the lowest level of pain sensitivity was during ovulation (days 15-21) [85]. It is documented that the effect of variation in gonadal hormone levels across the menstrual cycle on female sensitivity to pain was small and had only a minor contribution to gender differences in pain [70].…”
Section: Biological Mechanismsmentioning
confidence: 84%
“…In contrast, a higher threshold and tolerances in the premenstrual phase have been found by Aberger et al [1983] who used the muscle ischaemia task [84]. It is revealed that that the highest level of pain sensitivity was one week following menstruation (days 1-7), and the lowest level of pain sensitivity was during ovulation (days 15-21) [85]. It is documented that the effect of variation in gonadal hormone levels across the menstrual cycle on female sensitivity to pain was small and had only a minor contribution to gender differences in pain [70].…”
Section: Biological Mechanismsmentioning
confidence: 84%
“…It is unlikely that the effects can be related to menstrual periods in the female subjects; even if such effects are not balanced by the selection methods, they are generally quite small, about 5 % to 10% of the mean (Procacci, Zoppi, Maresca, & Romano, 1974;Tedford et al, 1977).…”
Section: Gender Differences In Pain Responsivenessmentioning
confidence: 99%
“…Pain thresholds were at a minimum (most sensitive) during ovulation and at maximum (least sensitive) during menstruation. Tedford, Warren, and Flynn (1977) reported cyclic changes in shock aversion thresholds in the opposite direction. Maximum thresholds were obtained during ovulation and minimum, during menstruation.…”
Section: Resultsmentioning
confidence: 99%
“…However, a rhythm was reported in menopausal women and to some degree in young men. More recently, Tedford, Warren, and Flynn (1977) reported cyclic changes in the pain threshold in association with the menstrual phases. They did not use a traditional pain detection measure.…”
mentioning
confidence: 99%